Business plan - Gorochovský, Jaroslav (2020)
This bachelor thesis aims to create a realistic business plan of a newly developed technological product and guarantee its successful entry on the European market considering all important factors. Choice of the product is not accidental as it is a passion project of the author of thisthesis. Many sleepless nights were put into development, engineering and preparation of necessary patent documents and much more are to be spent in order to achieve the vision of creating an innovation in the field of external keyboards. The aim of this thesis is to assess viability of the proposed project.